Pengaruh Sistem Informasi Akuntansi Manajemen Dan Sistem Pengukuran Kinerja Terhadap Kinerja Manajerial Pada Unit Studi Kasus Pada PT. Sentosa Industri Plastik - Miftah Alaina Hammi; Hotbin Hasugian; Nuri Aslami (Akuntansi, 2023)
This research aims (1) to determine the partial influence of the management accounting information system on managerial performance in the Case Study unit at PT. Sentosa Plastic Industry Medan City (2) to determine the effect of the partial performance measurement system on managerial performance in the Case Study unit at PT. Sentosa Plastic Industry Medan City and (3) to determine the effect of the management accounting information system and performance measurement system simultaneously on managerial performance in the Case Study unit at PT. Sentosa Plastic Industry, Medan City. The type of research used is quantitative research. The population in this study were heads and employees at PT. Sentosa Plastic Industry as many as 58 people. The sampling technique used purposive sampling with a total sample of 30 respondents. Data collection techniques use questionnaires. The data analysis technique uses multiple linear regression analysis with the help of SPSS version 22.0 software. The research results show that first, the management accounting information system partially has a positive and significant effect on managerial performance with a t value of 3.325 > t table 2.052 and a significance value of 0.003 < 0.05. Second, the performance measurement system partially has a positive and significant effect on managerial performance with a calculated t value of 4.274 > t table 2.052 and a significance value of 0.000 < 0.05. Third, the management accounting information system and performance measurement system simultaneously have a positive and significant effect on managerial performance with a calculated F value of 17.369 > F table 3.35 and a significance value of 0.000 < 0.05.